2012
DOI: 10.1021/es203505g
|View full text |Cite
|
Sign up to set email alerts
|

Np(V) and Pu(V) Ion Exchange and Surface-Mediated Reduction Mechanisms on Montmorillonite

Abstract: Due to their ubiquity and chemical reactivity, aluminosilicate clays play an important role in actinide retardation and colloid-facilitated transport in the environment. In this work, Pu(V) and Np(V) sorption to Na-montmorillonite was examined as a function of ionic strength, pH, and time. Np(V) sorption equilibrium was reached within 2 h. Sorption was relatively weak and showed a pH and ionic strength dependence. An approximate NpO(2)(+) → Na(+) Vanselow ion exchange coefficient (Kv) was determined on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 46 publications
(98 reference statements)
7
89
0
Order By: Relevance
“…By contrast, reactions with redox active solid phases are usually found to proceed fast (Stumm, 1992;Buerge and Hug, 1999;Liger et al, 1999;Nakata et al, 2002;Charlet et al, 2007;Bach et al, 2014). Notably for reactions with Pu(V) with mineral surfaces rapid reduction to Pu(IV) is stated (Powell et al, 2004(Powell et al, , 2005Hixon et al, 2010;Kirsch et al, 2011;Zaravin et al, 2012). The time necessary for a complete Pu(V) reduction varies from few hours to few days depending on the mineral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, reactions with redox active solid phases are usually found to proceed fast (Stumm, 1992;Buerge and Hug, 1999;Liger et al, 1999;Nakata et al, 2002;Charlet et al, 2007;Bach et al, 2014). Notably for reactions with Pu(V) with mineral surfaces rapid reduction to Pu(IV) is stated (Powell et al, 2004(Powell et al, , 2005Hixon et al, 2010;Kirsch et al, 2011;Zaravin et al, 2012). The time necessary for a complete Pu(V) reduction varies from few hours to few days depending on the mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction is, however, also found at mineral surfaces where a specific reducing partner is absent (Hixon et al, 2013), suggesting that Pu(IV) under given conditions simply is the thermodynamically favored species. Zaravin et al (2012) studied Np(V) sorption onto montmorillonite under the same conditions as for Pu(V), but did not observe Np(V) reduction. This observation can be explained by the fact that the standard redox potential of the Np(V)/Np(IV) couple (E 0 NpO þ 2 =Np 4þ ¼ 0:604 V) is lower than that of the Pu(V)/Pu(IV) pair E PuO þ 2 =Pu 4þ ¼ 1:031 V (Guillaumont et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Under aerobic conditions and at circumneutral pH values, Np(V) sorption to montmorillonite is likely to be dominated by surface complexation at the variably charged sorption sites (Bradbury and Baeyens, 2006;Turner et al, 1998b). However, at pH values below pH 6, cation exchange is expected to be the dominant sorption mechanism (Bradbury and Baeyens, 2006;Kozai et al, 1996;Nagasaki and Tanaka, 2000;Sabodina et al, 2006;Sakamoto et al, 1990;Turner et al, 1998b;Zavarin et al, 2012). Sorption by ion exchange is dependent on the composition of the clay exchange sites (Jensen, 1973), commonly occupied by Na + , K + , Mg 2+ and Ca 2+ , which is, in turn, strongly dependent on the aqueous conditions and electrolyte composition.…”
Section: Np Reactive Transportmentioning
confidence: 99%
“…However, up to now no sorption data for americium and plutonium on OPA have been published. More sorption studies have been reported for the uptake of actinides by pure clay minerals, that are the main constituents of OPA (e. g., montmorillonite [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], illite [32][33][34][35][36][37][38][39][40], kaolinite [31,[41][42][43][44][45][46][47][48][49][50][51] , the cation exchange capacity was equal to 10 ± 4 meq/100 g for both powders [9,11]. The mineral composition and the content of the trace elements of the used OPA measured by X-ray fluorescence analysis are given elsewhere [11].…”
Section: Introductionmentioning
confidence: 99%